On hyperholomorphic functions of the space variable - Gerus, O. F. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
For quaternionic-differentiable functions of a spatial variable, we prove a theorem on an integral over a closed surface. This theorem is an analog of the Cauchy theorem from complex analysis.